2012
DOI: 10.1016/j.jcin.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty Status on Survival After Transcatheter Aortic Valve Replacement in Older Adults With Severe Aortic Stenosis

Abstract: Objectives This study sought to evaluate the impact of frailty in older adults undergoing transcatheter aortic valve replacement (TAVR) for symptomatic aortic stenosis. Background Frailty status impacts prognosis in older adults with heart disease; however, the impact of frailty on prognosis after TAVR is unknown. Methods Gait speed, grip strength, serum albumin, and activities of daily living status were collected at baseline and used to derive a frailty score among patients who underwent TAVR procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
345
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 424 publications
(359 citation statements)
references
References 32 publications
8
345
1
5
Order By: Relevance
“…Four studies involved patients having cardiac valve surgery (including transcatheter aortic valve repplacement). 4,[22][23][24] Five studies involved a mix of gastrointestinal surgical patients, [25][26][27] including abdominal 21 and other general surgery patients. 28 Two studies involved vascular surgical patients 29,30 and two involved surgical oncology patients with either gynecological neoplasms 31 or gastric adenocarcinoma.…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
“…Four studies involved patients having cardiac valve surgery (including transcatheter aortic valve repplacement). 4,[22][23][24] Five studies involved a mix of gastrointestinal surgical patients, [25][26][27] including abdominal 21 and other general surgery patients. 28 Two studies involved vascular surgical patients 29,30 and two involved surgical oncology patients with either gynecological neoplasms 31 or gastric adenocarcinoma.…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
“…It is associated with increased mortality, surgical site infections, length of hospital stay, increased healthcare expenditure, and readmission rates in patients presenting for a variety of major noncardiac surgeries 8, 9, 10, 11, 12. Frailty has also been reported as a risk factor for mortality, major adverse cardiac and cerebrovascular events, and increased length of hospital stay in cardiac surgical patients 1, 2, 13, 14, 15, 16. The cardiac surgery literature consists primarily of relatively small single‐center studies with limited follow‐up durations, and the epidemiological features of frailty remain to be elucidated in long‐term follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2014 AHA/ACC guideline for VHD, the Katz index and gait speed have been recommended as good assessment tools of patient frailty (3), although there are no standardized criteria for measuring patient frailty. Recently, several studies on a cohort of patients who underwent TAVR reported that patient frailty is strongly associated with long-term prognosis (4,5). However, all these studies were performed in a small number of patients at a single center.…”
Section: Introductionmentioning
confidence: 99%